Introduction: Debates on experience and empiricism in nineteenth century France - Antoine-Mahut, Delphine (2019)
The lasting effects of the debate over canon-formation during the 1980s affected the whole field of Humanities, which became increasingly engaged in interrogating the origin and function of the Western canon (Gorak 1991; Searle 1990). In philosophy, a great deal of criticism was, as a result, directed at the traditional narrative of seventeenth-and eighteenth-century philosophies—a critique informed by postcolonialism (Park 2013) as well as feminist historiography (Shapiro 2016). D. F. Norton (1981), L. Loeb (1981) and many others1 attempted to demonstrate the weaknesses of the tripartite division between rationalism, empiricism and critical philosophy.2 As time went on, symptoms of dissatisfaction with what has been called the “standard narrative” ( Vanzo 2013) and the “epistemological par-adigm” (Haakonssen 2004, 2006) only increased. Indeed, at present, a consensus has been reached that the narrative of the antagonism between “Continental rationalism” and “British empiricism”, and the consequent Aufhebung provided by “German critical philosophy,” has been unable to make sense of the complexity, variety and dynamics of early modern.